2017
DOI: 10.1016/j.matdes.2017.01.067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing conditions on the thermal and electrical conductivity of poly (butylene terephthalate) nanocomposites prepared via ring-opening polymerization

Abstract: Successful preparation of polymer nanocomposites, exploiting graphene-related materials, via melt mixing technology requires precise design, optimization and control of processing. In the present work, the effect of different processing parameters during the preparation of poly (butylene terephthalate) nanocomposites, through ring-opening polymerization of cyclic butylene terephthalate in presence of graphite nanoplatelets (GNP), was thoroughly addressed. Processing temperature (240°C or 260°C), extrusion time… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 63 publications
3
28
0
1
Order By: Relevance
“…The shear and compression strengths during the extrusion process alter the electrical properties. These ob servations, already reported in the literature, were related to the re duction of exfoliated graphene nanoplatelets aspect ratio [41] and/or re-agglomeration phenomenon [ 42]. The conductivity above the per colation threshold is thereby greatly reduced.…”
Section: Cb-ncmentioning
confidence: 56%
“…The shear and compression strengths during the extrusion process alter the electrical properties. These ob servations, already reported in the literature, were related to the re duction of exfoliated graphene nanoplatelets aspect ratio [41] and/or re-agglomeration phenomenon [ 42]. The conductivity above the per colation threshold is thereby greatly reduced.…”
Section: Cb-ncmentioning
confidence: 56%
“…Reductions in M v (with respect to neat pCBT) have been observed for nanocomposites prepared via ring-opening polymerization in the presence of nanoflakes for similar pCBT nanocomposites. 34 Indeed, it is well-known that M w affects the crystallization rate of polymers, although the correlation is complex, 43 , 44 and so far no studies on the crystallization of pCBT with different M w have been reported in the literature.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This isoconversional integral method is based on the Coats–Redfern approximation of the temperature integral. It was exposed that ln(β/T2)=ln[ AR/Eg(α) ]E/(RT) …”
Section: Methodsmentioning
confidence: 99%